Effects of chronic mild stress on parameters of bone assessment in adult male and female rats - Valente, Fabricio L.; Ferreira, Anna Paula B. R.; Costa, Leonardo D. da [UNESP]; Louzada, Mario J. Q. [UNESP]; Patarroyo, Joaquin H.; Vargas, Marlene I. (Revista Pesquisa Veterinaria Brasileira, 2016)
Osteoporosis is a multi factorial disease of high prevalence and has great impact on quality of life, because the effects on bone structure increase the risk of fractures, what may be very debilitating. Based on the observation that patients with depression have lower bone mineral density than healthy individuals, many studies have indicated that stress could be an aggravating factor for bone loss. This study evaluates the effect of a protocol of chronic mild stress (CMS) on parameters of bone assessment in male and female rats. Five 5-monh-old rats of each sex underwent a schedule of stressor application for 28 days. Stressors included cold, heat, restraint, cage tilt, isolation, overnight illumination, and water and food deprivation. Five rats of each sex were kept under minimum intervention as control group. The animals were weighed at beginning and end of the period, and after euthanasia had their bones harvested. Femur, tibia and lumbar vertebrae were analyzed by bone densitometry. Biomechanical tests were performed in femoral head and diaphysis. Trabecular bone volume was obtained from histomorphometric analysis of femoral head and vertebral body, as well as of femoral midshaft cross-sectional measures. Not all parameters analyzed showed effect of CMS. However, tibial and L4 vertebral bone mineral density and cross-sectional cortical/medullar ratio of femoral shaft were lower in female rats submitted to the CMS protocol. Among male rats, the differences were significant for femoral trabecular bone volume and maximum load obtained by biomechanical test. Thus, it could be confirmed that CMS can affect the balance of bone homeostasis in rats, what may contribute to the establishment of osteopenia or osteoporosis.
Keywords: Stress; osteoporosis; animal model; bone densitometry; bone histomorphometry; rat